Fungsi Kewirausahaan Dalam Pendidikan - Seli Damayanti Damayanti; Anne Effane (KARIMAH TAUHID, 2022)
In its development, the formation of entrepreneurial values is not only among entrepreneurs and the business world but has added to the world of education, where activities also really need an entrepreneurial spirit. Entrepreneurship in education aims to make humans holistically, as humans who have the character, understanding and skills as entrepreneurs. Basically entrepreneurship educators are carried out by school principals, teachers and education staff (counselors), educators of course as an educational community. Entrepreneurship educators apply the curriculum by identifying several types of school activities in schools that can realize entrepreneurship education itself and also for students in everyday life. In this case, entrepreneurship education programs in schools can be internalized through various points that are integrated in all entrepreneurship subjects. Entrepreneurship education is integrated into extra-curricular activities, entrepreneurship through self-development, changes in the implementation of entrepreneurship learning from practice to theory, integration of entrepreneurship subjects. Entrepreneurship education into handbooks, integration of Entrepreneurship education through school culture, integration of Entrepreneurship education through local subjects.